Old Before their Time: The Role of Employers in Retirement Decisions - Piera Bello; Vincenzo Galasso (Center for Economic Studies and ifo Institute (CESifo), 2015)
Do elderly workers retire early voluntarily, or are they induced (or even forced) by their employees? To establish the relevance of the labor demand component in retirement decisions, we consider a trade liberalization between Switzerland and the EU – the Mutual Recognition Agreement (MRA). A vast literature suggests that these trade liberalizations induce firms to relocations and to restructure, with large compositional effects on the labor market particularly for the elderly workers, who face higher mobility costs. Using Swiss Labor Force Survey data, we use a difference in differences approach to compare early retirement behavior in three periods (pre-liberalization, announcement, and implementation) for three groups of industries. MRA industries represent our treatment group; control groups are non-MRA manufacturing industries, and services. Our empirical results show that elderly workers are more likely to retire early in the MRA sector during the announcement period, and that the employment of young (30-years old) male workers increases. The distribution of wages by age is instead unaffected. Additional empirical evidence using Swiss Business Census and UN Comtrade data suggests that the increase in early retirement in MRA is not explained by more firms' exits, nor by more early retirement among the exiting firms. It is rather the surviving MRA firms, which react to the increase in competition by adjusting their labor force and use more early retirement.
Keywords: J14; J23; J26; H55; 330; early retirement; firms' restructuring; labor demand of elderly workers